The fixed wage puzzle: Why profit sharing is so hard to implement - Jürgen Jerger; Jochen Michaelis (Osteuropa-Institut Regensburg, 2010)
It is well known that profit sharing arrangements Pareto-dominate fixed wage contracts. Share agreements are (far) less than ubiquitous, however. This paper offers a solution of this fixed wage puzzle by adopting a perspective of bounded rationality. We show that share arrangements that fulfill plausible constraints are not generally acceptable to both firms and unions.
Keywords: 330; Lohnbildung; Erfolgsbeteiligung; Lohnverhandlungen; Beschränkte Rationalität; Theorie